Exploring Occupational Stress Among Intensive Care Units Nurses in Saudi Arabia Using the Health and Safety Executive Management Standards Indicator Tool - Ageel M; Shbeer A (Dove Medical Press, 2022)
Mohammed Ageel, Abdullah Shbeer College of Medicine, Jazan University, Jazan, 45142, Saudi ArabiaCorrespondence: Abdullah Shbeer, College of Medicine, Jazan University, Jazan, 45142, Saudi Arabia, Tel +966505769570, Email ashbeer@jazanu.edu.saBackground: Work in intensive care units (ICU) is associated with high levels of stress, which can result in reduced productivity and compromised health care quality, if not managed appropriately. The Health and Safety Executive (HSE) has developed the Management Standards Indicator Tool (IT) that includes the six HSE Management Standards; demands (workload, work patterns and environment), control (how much say a person has in the way they work), manager support (encouragement, sponsorship, resources provided by organization/line management) and peer support (encouragement and resources from colleagues), workplace relationships (promoting positive working to avoid conflict and deal with unacceptable behavior), roles (whether people understood their role), and change (how organizational change is managed). This study aimed to assess occupational stress and identify the major management standards indicators of organizational psychosocial hazard exposure among ICU nurses in public hospitals in Jazan, Saudi Arabia, using the HSE-IT for occupational stress.Methods: The survey population included all full-time ICU nurses affiliated with the Jazan Region Health Administration. This study used a cross-sectional online survey based on the HSE-IT, which assesses the six HSE Management Standards representing potential stress hazards. The mean scores were interpreted in relation to the HSE benchmarks. It also included a qualitative component in the form of narrative comments regarding the most common sources of occupational stress and recommendations to reduce this stress. The data were analyzed to obtain descriptive and inferential statistics. The demographic variables examined for their association with the HSE-IT Standards.Results: A total of 120 responses were collected from ICU nurses, with a response rate of 66%. The nurses were primarily female (53.3%) and aged between 25 and 34 years (60.0%). They had bachelor's degrees (61.7%) and between 6 and 10 years of experience (55.0%). Most of them lived in urban settings (75.0%), were married (60.0%), and earned between 10,000 and 15,000 Saudi riyals per month (41.7%). In terms of weekly overtime, 66.7% of them did fewer than 5 hours. The results show that in relation to the HSE benchmarks, "good but needs improvement" was indicated in the change standard, "clear need for improvement" was indicated in the demands, peer support and relationships standards, "urgent action needed" was indicated in the control, manager support and roles standards. The qualitative data revealed that the most cited source of occupational stress was unsupportive management. Consequently, the most commonly proposed recommendation to reduce such stress was better management. The associations between sociodemographic characteristics, place of residence and overtime working hours, and the HSE Management Standards were commonly observed.Conclusion: The findings of this study indicate that the risks associated with occupational stress for ICU nurses are not being optimally managed and that the standards are not being achieved. The study suggests that a psychologist-designed and -led staff stress management intervention should be adopted in ICUs, with regular evaluations being undertaken to track the implemented changes and identify any shortcomings.Keywords: occupational stress, nursing practice, intensive care, nurses